2017
DOI: 10.1021/acs.nanolett.6b03727
|View full text |Cite
|
Sign up to set email alerts
|

Growth of All-Wurtzite InP/AlInP Core–Multishell Nanowire Array

Abstract: We demonstrated the formation of all-wurtzite (WZ) InP/AlInP core-multishell (CMS) nanowires (NWs) by selective-area growth with the crystal structure transfer method. The CMS NWs consisting of an AlInP-based double heterostructure showed that the crystal structure of the multishell succeeded to the WZ phase from the WZ InP NW by the crystal structure transfer method. Transmission electron microscopy revealed that the core-shell interface had a few stacking faults due to lattice mismatch. In addition, lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…In a later work, the same group presented a detailed loss efficiency analysis together with some guidelines to make larger improvements in the LED performance . Quite recently, crystal phase engineering of NW growth , enabled wurtzite phosphide materials that has been employed to develop AlInP NWs with strong, room temperature emission in the green gap . With respect to axial current injection schemes, Scofield et al reported on a n-GaAs/i-InGaAs/p-GaAs axial heterostructure with GaAsP diffusion barriers to provide enhanced carrier confinement, providing a 5-fold increase in output intensity.…”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
“…In a later work, the same group presented a detailed loss efficiency analysis together with some guidelines to make larger improvements in the LED performance . Quite recently, crystal phase engineering of NW growth , enabled wurtzite phosphide materials that has been employed to develop AlInP NWs with strong, room temperature emission in the green gap . With respect to axial current injection schemes, Scofield et al reported on a n-GaAs/i-InGaAs/p-GaAs axial heterostructure with GaAsP diffusion barriers to provide enhanced carrier confinement, providing a 5-fold increase in output intensity.…”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
“…As schematically shown in Figure a, the InP shell layer was grown to a thickness of about 10 nm in the radial direction to form the InGaAs/InP core–shell NWs. To facilitate shell growth, , the V/III material supply ratio was set higher and the growth temperature was lowered to 580 °C after the growth of InGaAs NWs (see the Supporting Information for details). Considering the In composition in the core (about 50–51%) and the thickness of the InP shell, the coherency of the lattice in the whole NW was maintained, and the InGaAs core was subject to the tensile strain.…”
mentioning
confidence: 99%
“…Heurlin et al reported WZ InP/InGaAs NW core–shell heterostructures with light emission at ∼1.4 μm . Ishizaka et al have successfully grown WZ InP/GaP core–shell NWs, InP/AlGaP core–shell NWs, and InP/AlInP core–shell NWs for green light emission by employing the core WZ InP NW as a template to transfer the crystal structure to radially grown heterostructures. Recently Chang-Hasnain’s group reported optically pumped lasing at ∼1.3 μm and array LEDs with ∼1.5 μm from core–shell InGaAs/InP MQW nanopillars grown on Si by the SAE technique, demonstrating a great potential for achieving InGaAs QW-NW devices for optical communications.…”
mentioning
confidence: 99%